2018
DOI: 10.21608/mnj.2018.149711
|View full text |Cite
|
Sign up to set email alerts
|

Parasitic Infestation and Its Effect on Growth of Primary School Children in Hehia Center, Zagazig City, Sharkia Governorate

Abstract: Background: Intestinal parasitic infestations are one of the neglected tropical diseases and it is most common among school children. It negatively affects children growth, cognitive development and learning abilities. It may lead to nutritional deficiencies and anemia. The present study aims to identify the effect of parasitic infestations on growth among primary school children. Descriptive comparative design was conducted on a sample of 200 children (100 infected study group, and 100 not infected) at Hehia … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
4
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 3 publications
2
4
1
Order By: Relevance
“…Our findings were consistent with the study's findings regarding the association between intestinal parasites and clinical symptoms at the time of examination, which indicated that the majority of infected children experienced abdominal pain, dysentery, vomiting, perianal itching, diarrhea, and pallor (69.9%, 9.1%, 3.2%, 33.9%, 12.9%, and 48.4%, respectively), with a highly significant statistical difference [25]. Most of these symptoms were general signs of abdominal discomfort like nausea, vomiting, diarrhea, loss of appetite, and weight loss.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Our findings were consistent with the study's findings regarding the association between intestinal parasites and clinical symptoms at the time of examination, which indicated that the majority of infected children experienced abdominal pain, dysentery, vomiting, perianal itching, diarrhea, and pallor (69.9%, 9.1%, 3.2%, 33.9%, 12.9%, and 48.4%, respectively), with a highly significant statistical difference [25]. Most of these symptoms were general signs of abdominal discomfort like nausea, vomiting, diarrhea, loss of appetite, and weight loss.…”
Section: Discussionsupporting
confidence: 92%
“…In consensus, it was reported that there were greater infection rates in male cases (66.6%) compared to female cases (41.4%) [ 22 ]. In internal reports [ 25 ] as in Tanta city in Egypt and in external reports [ 20 ] as in Debre Berhan town in Ethiopia, male children had greater rates of intestinal parasitic infections. On the other hand, some studies claim that female individuals had a higher rate of intestinal parasite infection than male participants [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations